Analisis Pengaruh Word Of Mouth, Iklan Dan Citra Merek Terhadap Keputusan Pembelian Melalui Minat Beli Sebagai Variabel Intervening Pada Smartphone Xiaomi Manado - Kojongian, Rivan (Universitas Sam Ratulangi, 2019)
The results showed that word of mouth had a positive and significant influence on buying interest. Advertisements are positive and significant interests in buying interest. Imagery manipulates positive and significant interest in buying. Word of mouth has a positive and significant effect on purchasing decisions. Advertisements are not significant for purchasing decisions. Brand image is significant to purchasing decisions. The interest in buying has a significant impact on Word of mouth purchasing decisions that significantly influence purchasing decisions through buying offers. Advertising is not important for purchasing decisions through buying brand purchases is not important for purchasing decisions through purchase purchases.Keywords: Word of Mouth, Advertising, and Brand Image, Consumer Decision Making, Buying Interest